Effect of integrated weed management practices on fibre yield of rainfed Mesta in North Coastal Andhra Pradesh - Malleswari Sadhineni,; T. Sreelatha,; S. Mitra, (Annals of Agricultural Research, 2023)
A Field experiment was conducted at AINP on Jute and Allied Fibres, Agricultural Research Station, Amadalavalasa, Andhra Pradesh to evaluate chemical, mechanical, cultural practices and their integration for effective weed management in Mesta during kharif 2021. The results revealed that, maximum fibre yield of mesta was recorded in the weed free check (2093 kg/ha) followed by two hand weeding (HW) (1844 kg/ ha) and Quizalofop ethyl 10% EC @ 38 g/ha at 15 days after emergence (DAE) + one hand weeding (HW) at 30 DAE (1828 kg/ha). However, mesta + greengram (1:1) intercropping recorded mesta equivalent yield of 1892 kg/ha which was statistically at par with weed free check (2093 kg/ha) and both the treatments recorded significantly higher fibre yield of mesta over other treatments.Two HW at 15 and 35 DAE (27.3 g/m2 ), Quizalofop ethyl 10% EC @ 38 g/ha at 15 DAE (POE) + one HW at 30 DAE (53.3 g/m2 ) and mulching with rice straw @ 7.5 t/ha + one HW at 15-21 DAE (53.7 g/m2 ) recorded lowest weed dry matter at harvest. Weed control efficiency (WCE) was highest with weed free check (99.3%) followed by two HW at 15 and 35 DAE (94.4%), Quizalofop ethyl 10% EC @ 38 g/ha at 15 DAE (POE) + one hand weeding (HW) at 30 DAE and mulching with rice straw @ 7.5 t/ha + one HW at 15-21 DAE treatment also recorded 89.1% WCE at harvest